An unexpected gateway: The particularities of Mauritius as a hub in oil and gas GPNs. Issue 1 (2nd January 2021) - Scholvin, Sören; Breul, Moritz
ABSTRACT: The periphery of the world economy is integrated into global production networks (GPNs) by 'gateways'. These are intermediary places from where transnational corporations organise their business activities in close cooperation with corporate service providers. Gateways may also serve as logistics nodes as well as sites of industrial processing and knowledge generation. While some claim that gateways are engines of growth, others argue that they prosper at the expense of peripheral places. The article applies these thoughts to Mauritius, oil and gas GPNs, and the gateway's impact upon sub-Saharan Africa. The analysis indicates that Mauritius holds a certain potential for logistics and corporate control. The island serves as a hub of service provision already today. Only its status as a tax haven has a negative effect on resource peripheries. Against the backdrop of these findings, the authors discuss whether gateways should be seen as drivers or obstacles of peripheral development.